(a) UV-vis spectra of 25 mg/L of MB solution before and after treatment with Fe3O4, PS powder, and different Fe3O4/PS composites, and (b) the effect of the type of adsorbent on the removal efficiency. - Tamer S. Saleh (5181146) (2025)
(a) UV-vis spectra of 25 mg/L of MB solution before and after treatment with Fe3O4, PS powder, and different Fe3O4/PS composites, and (b) the effect of the type of adsorbent on the removal efficiency.